2003
DOI: 10.1097/01.tp.0000045056.82561.0f
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor receptor inhibition reduces allograft arteriosclerosis of heart and aorta in cholesterol-fed rabbits

Abstract: The results of the present study suggest that PDGF-R activation may regulate the development of transplant and accelerated arteriosclerosis in hypercholesterolemic rabbits. Thus, PTK inhibitors may provide new strategies for prevention of these fibroproliferative vascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This prompted us to embark on early studies of an experimental compound, currently known as imatinib mesylate (Glivec), which was developed as a selective inhibitor of the v-Abl, c-Kit and PDGF-R tyrosine kinases. Using this compound at well-tolerated doses (5–50 mg/kg/day) in preclinical models, we demonstrated virtually complete suppression of neointimal hyperplasia triggered by mechanical injury [29], as well as a 50% reduction in TA in cardiac [27, 28] and vascular [28] allografts (relative to cyclosporin A monotherapy). Other recent studies from our laboratory have shown considerable benefit in using this agent in rat models of obliterative bronchiolitis [40] and chronic allograft nephropathy [41].…”
Section: Discussionmentioning
confidence: 99%
“…This prompted us to embark on early studies of an experimental compound, currently known as imatinib mesylate (Glivec), which was developed as a selective inhibitor of the v-Abl, c-Kit and PDGF-R tyrosine kinases. Using this compound at well-tolerated doses (5–50 mg/kg/day) in preclinical models, we demonstrated virtually complete suppression of neointimal hyperplasia triggered by mechanical injury [29], as well as a 50% reduction in TA in cardiac [27, 28] and vascular [28] allografts (relative to cyclosporin A monotherapy). Other recent studies from our laboratory have shown considerable benefit in using this agent in rat models of obliterative bronchiolitis [40] and chronic allograft nephropathy [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PDGFR inhibitors such as imatinib and AG-1295 are effective in suppressing restenosis and stenosis in experimental animals (Myllarniemi et al, 1999;Fishbein et al, 2000;Sihvola et al, 2003;Levitzki, 2005). Inhibition of PDGFR in VSMCs by imatinib and AG-1295 requires micromolar concentrations (Fishbein et al, 2000;Sanz-Gonzalez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Besides Bcr-Abl and c-Kit, imatinib also inhibits PDGFR tyrosine kinase Druker et al, 1996). Experiments in animals have shown that imatinib inhibits restenosis after balloon angioplasty and stenosis after allograft (Myllarniemi et al, 1999;Sihvola et al, 2003). Inhibition of PDGFR by imatinib, however, requires micromolar concentrations in cell-based assays Sanz-Gonzalez et al, 2004).…”
mentioning
confidence: 99%
“…Despite the universal occurrence of atherosclerosis in the world, the pathogenesis of disease remains incompletely understood. Atherosclerosis can be considered to be a modified form of chronic inflammation induced by lipids (Glass and Witztum, 2001), and many have followed in this path including evidences that numerous cell adhesion molecules and growth factors were determined in the atherosclerotic plaques (Blankenberg et al, 2003;Sihvola et al, 2003).…”
Section: Introductionmentioning
confidence: 99%